2006
DOI: 10.1063/1.2425041
|View full text |Cite
|
Sign up to set email alerts
|

High-density, uniform InSb∕GaSb quantum dots emitting in the midinfrared region

Abstract: The authors have developed a multistep molecular-beam epitaxy growth technique which allows them to grow InSb quantum dots with high structural perfection and high density. This technique consists in the deposition at a very low temperature followed by a properly designed annealing step. Fully strained InSb∕GaSb quantum dots with a density exceeding 7×1010cm−2 and lateral sizes in the 20–30nm range have been obtained. Narrow photoluminescence emission is obtained around 3.5μm up to room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…A good candidate is InSb/GaSb, for which a 2D ∼ 30 nm. QDs based on InSb/GaSb with lateral sizes in the range 20 − 30 nm [33] or even smaller, of the order of 10 nm [34], have been grown by molecular-beam epitaxy. As we pointed out before, the intensity values for which our approach is valid should be in the range 10 7 − 10 12 W/cm 2 for commonly used laser frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…A good candidate is InSb/GaSb, for which a 2D ∼ 30 nm. QDs based on InSb/GaSb with lateral sizes in the range 20 − 30 nm [33] or even smaller, of the order of 10 nm [34], have been grown by molecular-beam epitaxy. As we pointed out before, the intensity values for which our approach is valid should be in the range 10 7 − 10 12 W/cm 2 for commonly used laser frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…No threading dislocations are observed in contrast to the previous results obtained for usual MBE growth conditions. By tilting the sample to get the interface inclined to the electron beam and to adjust g = 220 diffraction conditions we have demonstrated that the InSb QDs are perfectly coherent and are very uniform in size [34].…”
Section: The (Ga)insb/gasb Systemmentioning
confidence: 99%
“…Such an element playing a role similar to a surfactant, it can be considered as a virtual-surfactant, or self-surfactant [28,29]. In such a situation however, the impact of a 2D growth can be either positive, as in the case of (Ga,In)(N,As)(Sb) QWs growth on GaAs [10,45,46], or negative as in the case of InSb QDs growth on GaSb [33,34]. The growth conditions must thus be precisely adjusted in accordance with the target.…”
Section: Surfactants In Iii-v Semiconductor Epitaxymentioning
confidence: 99%
“…To penetrate in the long-wavelength region (l42 mm) it needs to produce quantum dots based on the narrow-gap semiconductors such as InSb and InAsSb solid solutions obtained in InAs or GaSb enriched matrix that are prospective for the fabrication of emitters and detectors, which can operate in mid-infrared spectral range 3-4 mm [7]. It would be paid an attention that the lattice mismatch between InSb and InAs binary compounds is 7% that is similar to the InAs/GaAs quantum dots system described elsewhere [8].…”
Section: Introductionmentioning
confidence: 99%